Effects of electroplated zinc-nickel alloy coatings on the fatigue strength of AISI 4340 high-strength steel - Voorwald, HJC; Miguel, I. M.; Peres, M. P.; Cioffi, MOH (Asm International, 2005)
Recovered substrates have been extensively used in the aerospace field. Cadmium electroplating has been widely applied to promote protective coatings in aeronautical components, resulting in excellent corrosion protection combined with a good performance in cyclic loading. Ecological considerations allied to the increasing demands for corrosion resistance have resulted in the search for possible alternatives. Zinc-nickel (Zn-Ni) alloys have received considerable interest recently, because these coatings show advantages such as a good resistance to white and red rust, high plating rates, and acceptance in the market. In this study, the effect of electroplated Zn-Ni coatings on AISI 4340 high-strength steel was analyzed for rotating bending fatigue strength, corrosion, and adhesion resistance. The compressive residual stress field was measured by x-ray diffraction prior to fatigue tests. Optical microscopy documented coating thickness, adhesion characteristics, and coverage extent for nearly all substrates. Fractured fatigue specimens were investigated using scanning electron microscopy (SEM). Three different Zn-Ni coating thicknesses were tested, and comparisons with the rotating bending fatigue data from electroplated Cd specimens were performed. Experimental results differentiated the effects of the various coatings on the AISI 4340 steel behaviour when submitted to fatigue testing and the influence of coating thickness on the fatigue strength.
Keywords: cadmium electroplating; corrosion; fatigue; zinc-nickel coatings